Comparison of Faculty and Student Perceptions of Videos in the Online Classroom - Valenti, Elizabeth; Feldbush, Tennille; Mandernach, Jean (Journal of University Teaching and Learning Practice, 2019)
While instructors and students generally value the integration of videos in the online classroom, there are a number of practical considerations that may mediate the utility of videos as a teaching and learning tool. The current survey examines faculty and student perceptions of videos in the online classroom with an emphasis on the practical factors that influence video integration. Results indicate differences in faculty and student acceptance and endorsements of videos for content presentation compared to assignment feedback. Faculty desire more opportunities to interact with their students (i.e., video-based discussions, video-conferencing, and student-generated videos) and highlighted efficiency as a key consideration. Students emphasized a desire for multiple opportunities to engage with course material; while students value text-based resources, they also want to have options to learn and interact via video and audio. Key to student recommendations is an awareness of the time involved to engage with online videos. Discussion highlights practical approaches to maximize the value and utility of videos in the online classroom.